If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = 2d + 6 Reorder the terms: 20 = 6 + 2d Solving 20 = 6 + 2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2d' to each side of the equation. 20 + -2d = 6 + 2d + -2d Combine like terms: 2d + -2d = 0 20 + -2d = 6 + 0 20 + -2d = 6 Add '-20' to each side of the equation. 20 + -20 + -2d = 6 + -20 Combine like terms: 20 + -20 = 0 0 + -2d = 6 + -20 -2d = 6 + -20 Combine like terms: 6 + -20 = -14 -2d = -14 Divide each side by '-2'. d = 7 Simplifying d = 7
| 4x-28/3=3x+21/4 | | n(n+1)(n-2)(n+4)=84 | | 8x+5x=143 | | 2x^2+x+0=0 | | 3x-5=10-47 | | -2+9=21 | | 4x-28/3 | | 1.75x+1.00=13.75 | | 7x+26=3x+74 | | 5y^2+5x+10y+1=0 | | -5k-4=-19 | | 11-7x=71-21x | | 2.5x^2+8.5x=0 | | 25x^2+85x=0 | | 2x-10y=-10 | | 7(x-5)=7x-35 | | 6(x+3)=9-2[x-4(x+1)] | | h=235t-16t^2 | | 62.5= | | 23*y=7385526 | | 2x^2-14=12x | | 6=s/9 | | 9=1.5z | | 3x+2=4p-7 | | a^2+16a+63=0 | | 24z=4z^2 | | y+1=-3/2(x+7) | | 5x/6-5/2=-10/9 | | -6x-6=8 | | x-2/2+x=3x | | -4u-5=11 | | -(3y+1)-(-2y+7)=5 |